2012
DOI: 10.1007/s10571-012-9815-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Cellular Prion Protein in the Neuron Adaptation Strategy to Copper Deficiency

Abstract: Copper transporter 1 (CTR1), cellular prion protein (PrP(C)), natural resistance-associated macrophage protein 2 (NRAMP2) and ATP7A proteins control the cell absorption and efflux of copper (Cu) ions in nervous tissues upon physiological conditions. Little is known about their regulation under reduced Cu availability, a condition underlying the onset of diffused neurodegenerative disorders. In this study, rat neuron-like cells were exposed to Cu starvation for 48 h. The activation of Caspase-3 enzymes and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 89 publications
3
11
1
Order By: Relevance
“…The upregulation of PrP expression and subsequent enhancement of Cu uptake was detected under reduced Cu availability, explained as the mechanism to sustain the copper delivery for Cu/Zn SOD (Urso et al, 2012). These results are in contrast with our data, since we have found out /1 are more sensitive to copper, manganese and nickel toxicity.…”
Section: Discussioncontrasting
confidence: 99%
“…The upregulation of PrP expression and subsequent enhancement of Cu uptake was detected under reduced Cu availability, explained as the mechanism to sustain the copper delivery for Cu/Zn SOD (Urso et al, 2012). These results are in contrast with our data, since we have found out /1 are more sensitive to copper, manganese and nickel toxicity.…”
Section: Discussioncontrasting
confidence: 99%
“…The presence of blebs at the margins of the aggregates can suggest an apoptotic induction, as confirmed by the observed reduction of the proliferation rate ( Fig. 7): this result could also be explained by the well-known protection role of PrP protein against oxidative stress (13,15). Previous studies performed in spheroids derived from prostatitis tumor cells showed that mitochondrial generated ROS induce an increase of PrP protein expression and its cellular colocalization with mitochondrial enzymes such as superoxide dismutase (SOD1) and catalase (75).…”
Section: Discussionsupporting
confidence: 57%
“…Thanks to a rapid constitutive clathrin-/cavolein-dependent process (9)(10)(11), PrP is endocyted and then recycled or degraded (12,13). The protein can also regulate intracellular copper content through its ability to bind the metal ions and promote their endocytosis (14)(15)(16)(17). In fact, the histidine residues present at the PrP N-terminal domain can bind up to 6 copper ions with low affinity (18)(19)(20) triggering their cellular internalization at the synaptic cleft (9,12,21,22).…”
Section: Introductionmentioning
confidence: 99%
“…High-affinity (range: ÎŒ M- n M ) copper-binding sequences, highly conserved in mammals, are localized N-terminally [185,186] and this strongly suggests the involvement of PrP C in the homeostasis of copper [187,188,189]. In particular, several pieces of evidence support the idea of proteins as copper transporters across the plasma membrane [189,190,191,192,193,194,195]. The endothelial expression of PrP C is a controversial but intriguing research topic, since blood vessels represent an ‘obligatory gate' for prions toward the central nervous system.…”
Section: Role Of Copper Transport Systems During Angiogenesismentioning
confidence: 99%